1215. Evaluation of the Carba-R NxG Assay in a Global Challenge Set of Pseudomonas aeruginosa. (31st December 2020) - Gill, Christian M; Asempa, Tomefa E; Tickler, Isabella A; Cruz, Caitlin dela; Tenover, Fred C; Nicolau, David P
Abstract: Background: Carbapenem-resistant P. aeruginosa (CRPA) is a growing clinical challenge. Carbapenemase production is particularly problematic due to high transmissibility and limited treatment options. Carbapenemase prevalence and diversity are largely driven by geography and thus testing spectrum will dictate utility in certain regions. The purpose of this study was to evaluate the performance of the research-use-only Xpert® Carba-R NxG (Carba-R NxG) and commercially available Xpert® Carba-R (Carba-R) in a global collection of P. aeruginosa . Methods: The challenge set included 123 clinical P. aeruginosa isolates from 11 countries. Isolates were previously categorized via PCR or whole-genome sequencing. Carbapenemase classes tested include: VIM, IMP, NDM, SPM, KPC, and GES. Non-carbapenemase (non-CP) harboring isolates were also tested (negative control). Isolates were tested using the Carba-R NxG and the Carba-R per manufacturer instructions. Carba-R NxG testing was completed by Cepheid (Sunnyvale, CA) blinded to genotype. Test performances were tabulated for each assay by carbapenemase class. Results: Both assays gave negative results for all non-CP isolates and positive results for all VIM, NDM, and KPC isolates. An improvement in IMP detection among isolates was observed (Carba-R NxG 100% vs. Carba-R 58% detection). All SPM and GES isolates, targets not present in the current Carba-R, were positive by Carba-R NxG. Two isolates harbored both VIM and GES, while a third isolate contained VIM and NDM. The Carba-R NxG identified both targets in all 3 isolates while the Carba-R was negative for both GES-containing isolates. Table 1 provides the test performance of both assays. Overall, the Carba-R NxG successfully categorized 100% of isolates tested compared with 68% for its predecessor. Table 1. Test performance of Carba-R NxG and Commercially Available Carba-R by Carbapenemase Class. Conclusion: As the prevalence and diversity of carbapenemase-producing CRPA continues to expand, the Carba-R offers a rapid and sensitive assay to identify clinically relevant carbapenemase genotypes to inform infection prevention and therapeutic interventions. The Carba-R NxG will expand the current targets including SPM, GES, NMC/IMI, and IMP-subtypes, outside the previous testing spectrum, increasing the global utility of the test. Disclosures: Isabella A. Tickler, BS, Cepheid (Employee) Caitlin dela Cruz, BS, Cepheid (Employee) Fred C. Tenover, PhD, Cepheid (Employee) David P. Nicolau, PharmD, Cepheid (Other Financial or Material Support, Consultant, speaker bureau member or has received research support.)Merck & Co., Inc. (Consultant, Grant/Research Support, Speaker's Bureau)Wockhardt (Grant/Research Support)